2010
DOI: 10.1007/s00572-010-0350-2
|View full text |Cite
|
Sign up to set email alerts
|

Ericaceous dwarf shrubs affect ectomycorrhizal fungal community of the invasive Pinus strobus and native Pinus sylvestris in a pot experiment

Abstract: This study aimed to elucidate the relationship between ericaceous understorey shrubs and the diversity and abundance of ectomycorrhizal fungi (EcMF) associated with the invasive Pinus strobus and native Pinus sylvestris. Seedlings of both pines were grown in mesocosms and subjected to three treatments simulating different forest microhabitats: (a) grown in isolation and grown with (b) Vaccinium myrtillus or (c) Vaccinium vitis-idaea. Ericaceous plants did not act as a species pool of pine mycobionts and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 57 publications
2
62
0
1
Order By: Relevance
“…Studies have hypothesized that when a Vaccinum understory promotes survival it is because of mycorrhizal facilitation; however, currently there is no evidence to support this hypothesis for whitebark pine. Greenhouse studies with Vaccinium and Pinus strobus L. have shown definitively that Vaccinium is not a source of mycorrhizal fungi for the pine since Vaccinium species associate with ericaceous fungi and pines with ectomycorrhizal fungi [49]. Interestingly, in the Kohout study, adjacent ericaceous plants did promote colonization of P. strobus root tips by the pine-specific ectomycorrhizal fungus Rhizopogon salebrosus A.H.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have hypothesized that when a Vaccinum understory promotes survival it is because of mycorrhizal facilitation; however, currently there is no evidence to support this hypothesis for whitebark pine. Greenhouse studies with Vaccinium and Pinus strobus L. have shown definitively that Vaccinium is not a source of mycorrhizal fungi for the pine since Vaccinium species associate with ericaceous fungi and pines with ectomycorrhizal fungi [49]. Interestingly, in the Kohout study, adjacent ericaceous plants did promote colonization of P. strobus root tips by the pine-specific ectomycorrhizal fungus Rhizopogon salebrosus A.H.…”
Section: Discussionmentioning
confidence: 91%
“…In many ecosystems, Ericaceae typically form undergrowth of EcM trees and considerable efforts have been invested in determining whether ericoid mycorrhizal and ectomycorrhizal plants share mycorrhizal partners. While a functional mycelial link between ErM and EcM plant has to this point not been demonstrated, rich ecological evidence has accumulated to suggest that such liaisons appear improbable [68], [69], [70]. To conclude, there is currently no evidence to suggest that EcM basidiomycetes detected in Ericaceae roots form functional ericoid mycorrhizae.…”
Section: Discussionmentioning
confidence: 99%
“…growing in the Seychelles Islands (Tedersoo et al 2007). Kohout et al (2010) also demonstrated that non-native Pinus strobus effectively adopted EMF assemblages with native fungi in a mesocosm experiment in Czech Republic. Similarly, Parladé et al (1996) demonstrated that 18 EMF species out of 27 collected in northern Spain were able to colonize roots of non-native Pseudotsuga menziesii in a pure culture test.…”
Section: Introductionmentioning
confidence: 96%